1985
DOI: 10.14219/jada.archive.1985.0250
|View full text |Cite
|
Sign up to set email alerts
|

Microwave sterilization

Abstract: This study has shown that representative fungi, viruses, and aerobic and anaerobic bacteria, including spore formers, can easily be killed in a conventional microwave oven with proper modifications. Metal instruments, including air turbine handpieces and burs, and acrylic dentures can be sterilized in short periods. Consistent sterilization can be accomplished only if the items to be sterilized are rotated in a three-dimensional manner throughout the microwave cavity. Arcing back to the magnetron and damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
0
16

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 18 publications
3
109
0
16
Order By: Relevance
“…However, chemical disinfection may present disadvantages like denture staining and patient's oral tissue reactions (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical disinfection may present disadvantages like denture staining and patient's oral tissue reactions (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Rohrer and Bulard (7) showed that microwave energy can easily kill microorganisms on denture acrylic resin surfaces within 15 min of exposure. Webb et al (8) reported that microwaving dentures at 350 W during 6 min may be a more effective method of sterilization than soaking the dentures in 0.02% sodium hypochlorite for 8 h.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave energy was introduced in 1985 for sterilization of nonautoclavable dental materials. It was shown that exposed to microwave energy for 10 minutes can kill microorganisms if the denture is attached to a three-dimensional rotating device (Rohler & Bulard, 1985). Lining materials have been found to be more prone to microbial adhesion than acrylic resin base materials and have been demonstrated to interact with oral microorganisms because of their surface texture and the physical/chemical affinity between the materials.…”
Section: Studies About the Effects Of Microwave Disinfectionmentioning
confidence: 99%
“…Denture disinfection has been recommended as an essential procedure for preventing crosscontamination and the maintenance of a healthy oral mucosa. The use of microwave irradiation to disinfect dentures and reliners has been suggested (Burns et al, 1990;Webb et al, 1998;Baysan et al, 1998;Thomas et al, 1995;Baysan et al, 1998;Webb et al, 1998) and stimulated as a disinfection model (Fitzpatrick et al, 1978;Lamb et al, 1983;Rohler et al, 1985;Jeng et al, 1987;Friedrich et al, 1988;Najdovski et al, 1991;Arikan et al, 1995;Atmaca et al, 1996;Lin et al, 1999;Kedjarune et al, 1999;Yeo et al, 1999;Nikawa et al, 2000;Jin et al, 2003;Pavarina et al, 2003;Gonçalves et al, 2006;Setlow, 2006;Gonçalves et al, 2007). Since that, researches have been developed in order to ensure the safe use of microwaving disinfection (Table 5).…”
Section: Studies About the Effects Of Microwave Disinfectionmentioning
confidence: 99%